Nomogram incorporating ultrasonic markers of endometrial receptivity to determine the embryo-endometrial synchrony after in vitro fertilization - He, Qi; Zhou, Ying; Zhou, Weiqin; Mao, Caiping; Kang, Qian; Pan, Yanping; Wang, Nan; Zhong, Yanyu; Pan, Zhansheng (Frontiers in Endocrinology, 2022)
Background A successful pregnancy using in vitro fertilization and embryo transfer (IVF-ET) requires a receptive endometrium, good-quality embryos, and a synchronized embryo-endometrial dialogue. Although embryo quality and endometrial receptivity (ER) have been fully assessed to exclude substandard conditions, the probability of successful ET is relatively low. Currently, embryo-endometrial synchrony is considered to be a possible explanation, because delayed, advanced, or narrowed window of implantation (WOI) may lead to ET failure. Objective This study aims to establish a nomogram incorporating a series of ultrasonic ER markers on the day before implantation to assess the embryo-endometrial synchrony, which may contribute to the improvement of clinical pregnancy outcomes. Methods Totally 583 women with 1135 complete IVF cycles were retrospectively analyzed. Among them, 357 women with 698 cycles and 226 women with 437 cycles were assigned to the training and validation cohorts, respectively. Ultrasonic ER markers obtained on the day before implantation were collected for analyses. In the training cohort, the screened correlates of clinical pregnancy failure were utilized to develop a nomogram for determining whether an infertile woman is suitable for the ET next day. This model was validated both in the training and validation cohorts. Results Spiral artery (SA) resistance index (RI), vascularisation index (VI), and flow index (FI) were independently associated with the ET failure (all P < 0.05). They were served as the components of the developed nomogram to visualize the likelihood of implantation failure in IVF-ET. This model was validated to present good discrimination and calibration, and obtained clinical net benefits both in the training and validation cohorts. Conclusion We developed a nomogram that included SA-RI, VI, and FI on the day before implantation. It may assist physicians to identify patients with displaced WOI, thus avoiding meaningless ET prior to implantation.